Karl Marx’s Contribution to Social and Political Philosophy - Islam, Md Khairul (Philosophy and Progress, 2024)
Karl Marx, the revolutionist philosopher, interpreted history as a world view which is the dimension of social development. His dialectic effort and materialistic conception are intended to preserve the rights of social being particularly of the working people who are repeatedly being oppressed. Class struggle is the ultimate solution of distinctions among classes through which there will be no class and the existing working class will revolt against capitalist economy and, as a result, they will control means of production which will create the situation of the dictatorship of the working people. These class distinctions will be removed through the establishment of scientific communism referred by Marx. This article shows how Marx’s life and thought changed the course of history and how he influenced society to make a better place for living. I intend to show the reasons behind the worldwide acceptance of Marxism theoretically. My aim is to show how his theories and ideas are significant in socio-political aspects of philosophy. Philosophy and Progress, Vol#73-74; No#1-2; Jan-Dec 2023 P 259-279